Efek Penggunaan Media Sosial Terhadap Perilaku Komunikasi Remaja - Azmiral Anwar; Rudi Salam; Lahmuddin Lahmuddin (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Social media has become an integral part of teenagers' lives, influencing how they communicate and interact. This research aims to understand the impact of social media on psychological changes in teenagers' communication behavior. This study uses a qualitative method with primary data sources from books. Data were collected through content analysis of books discussing the impact of social media on teenagers, particularly related to psychological aspects and communication behavior. The study found that social media has a significant influence on psychological changes in teenagers' communication behavior. This influence can be both positive and negative. Positive impacts include increased self-confidence, expanded social networks, and easier access to information. On the other hand, negative impacts include social anxiety, cyberbullying, and social media addiction. These findings provide important insights into how social media affects the psychological development and communication behavior of teenagers.